P-WAVE VELOCITIES OF POLYMINERALIC ROCKS: COMPARISON OF THEORY AND EXPERIMENT AND TEST OF ELASTIC MIXTURE RULES - Ji S.; Xia B.; Wang Q. (My University, 2003)
We compare the P-wave velocities (Vp) of 696 dry samples measured at pressures up to 0.6–1.0 GPa with values calculated from the volume fraction and room pressure elastic constants of each constituent mineral using 16 averaging methods. The exceptional large number of samples covers almost all common lithologic types of igneous and metamorphic rocks. The calculated Vp data are in good agreement with laboratory values measured at about 300 MPa, even though elastic constants of only 22 common minerals are used in the computation. The mean Vp of a polymineralic rock is exclusively controlled by the volume fractions of its constituent minerals while grain shape and crystallographic preferred orientations, anisotropy and other perturbations have minimum effects. The mean Vp can be fairly well predicted as long as a relevant mixture rule is used and the volume fraction is accurately determined for each mineral. However, none of the mixture rules can simultaneously produce the best fit to measured P-wave velocities for all the lithologic types. One method may work well for one lithology but poor for other lithology. Even for a given lithology, an averaging method may yield good agreement at moderate pressure but poor agreement at high pressure. Applications of an inappropriate mixture rule will potentially cause the misinterpretation of the crust and mantle Vp data in terms of mineralogical compositions and structures.
Keywords: Elasticity of polymineralic rocks; P-wave velocities; Elastic mixture rules